Fame at Last! : Belated Experimentalist Revisited - Drąg, Wojciech (Hungarian Journal of English and American Studies, 2021)
Book review: Jordan, Julia. Late Modernism and the Avant-Garde British Novel: Oblique Strategies. Oxford UP, 2020. 256 pages. ISBN 9780198857280. Hb. 80.00.